Improving Student Learning Outcomes with Problem-Based Learning on Islamic Civilization Material - Sri Istiqomah (Universitas Veteran Bangun Nusantara, 2022)
Historical events in the past should be a mirror for the present generation in the life of the nation and state. This material is contained in the teaching of history in high school. The teaching of history which is expected to provide insight into the development and progress of Islam in the past seems to be of little interest to students, this can be seen from the low completion results of students and their lack of understanding of history. The problem-based Learning model is one of the simple methods that the author believes is appropriate to be able to increase the value of Islamic cultural history lessons. The purpose of this study is to increase student enthusiasm for learning so that it will improve student learning outcomes as well, especially to improve student learning outcomes through a problem-based learning model on the subject of the development of Islamic civilization in class XI SMAN 7 Semarang. Research methods using Classroom Action Research, with the subject and location of the research in Class XI. The results of the study in the pre-cycle there was a completion of learning of 29.41%, in the first cycle there was an increase to 79.41%, and in cycle II the average student completion was 91.18%. The conclusion of learning research on the development of Islamic civilization in the heyday of Islam with the problem-based learning model can improve the ability of students.